The impact of low muscle mass on prognosis following neoadjuvant chemotherapy for resectable locally advanced rectal cancer: a systematic review and meta‐analysis. Issue 2 (17th February 2023) - Hatt, Jacob; Smart, Thomas F.F.; Hardy, Edward J.; Doleman, Brett; Lund, Jonathan N.; Philips, Bethan E.
Abstract: Background: Sarcopenia is characterized by the progressive and generalized loss of muscle mass and function. There is an increasing body of evidence to suggest that cancer patients with pre‐existing sarcopenia are at a greater risk of both short‐ and long‐term clinical complications. The aim of this review is to examine the impact of low muscle mass on prognostic outcomes in patients with locally advanced rectal cancer (LARC) who undergo neoadjuvant chemoradiotherapy (nCRT) prior to surgery. Methods: MEDLINE, PubMed, and Embase databases were searched from inception to October 2021. Any comparative studies relating to the prognostic outcomes of sarcopenic versus non‐sarcopenic patients with LARC who received nCRT prior to surgery were included. Risk of bias was assessed using the Risk Of Bias In Non‐randomized Studies of Interventions (ROBINS‐I). Meta‐analysis was performed on reported hazard ratios (HR) and 95% confidence intervals (CI) using DerSimonian–Laird random‐effects models. Results: A total of 598 patients from five studies were included in the analysis of hazard ratios for overall survival, whereas 505 patients from four studies were available for analysis of HR for disease‐free survival. Meta‐regression analysis showed a significant association between pre‐existing sarcopenia and worse overall survival (HR: 1.69, 95% CI: 1.15–2.48). The association between pre‐existing sarcopenia and shorter disease‐free survival was not statistically significant (HR: 1.07, 95% CI: 0.63–1.82). Conclusions: The review highlights the role that body composition can play on prognostic outcomes in patients undergoing multimodal cancer treatment. Given the complex underpinnings of sarcopenia progression, more research is needed to develop strategies to mitigate this impact in a physiologically vulnerable population.